A Comparative Study of Performance of SHGs Promoted by NGO and Panchayat - Debabrata Mondal and Debabrata Basu, (Indian Journal of Extension Education, 2014)
SHG is a very strong instrument to improve socio -economic standard of living, specially for the people living under thepoverty line and in the rural area. In such situation, a comparative research study was conducted in Tamluk sub-divisionof Purba -Midnapur district in West Bengal to determine the relative difference of the performance by the SHGs(panchayat promoted and NGO promoted SHGs) and impact analysis of micro finance programme. Data were collectedwith the help of structured interview schedules through personal interview method. The data were processed intofrequency and percentage. No significant differences were found between them in terms of their overall performances.However, the NGO-led SHGs performed better than panchayat-led SHGs in case of attributes like purpose of groupformation